The Mediating Role of Financial Governance on the Relationship Between Financial Management, Islamic Work Ethic and Accountability in Islamic Social Enterprise (ISE) - Muhammad Iqmal Hisham Kamaruddin; Nurul Aini Muhamed; Sofiah Md Auzair and Mohd Mohid Rahmat (Emerald Publishing Limited., 2024)
Indexed by WOS/SCOPUS/ERA